Robot-Assisted Deep Brain Stimulation: High Accuracy and Streamlined Workflow. Issue 3 (14th September 2022) - Giridharan, Nisha; Katlowitz, Kalman A.; Anand, Adrish; Gadot, Ron; Najera, Ricardo A.; Shofty, Ben; Snyder, Rita; Larrinaga, Christopher; Prablek, Marc; Karas, Patrick J.; Viswanathan, Ashwin; Sheth, Sameer A.
Abstract : BACKGROUND: A number of stereotactic platforms are available for performing deep brain stimulation (DBS) lead implantation. Robot-assisted stereotaxy has emerged more recently demonstrating comparable accuracy and shorter operating room times compared with conventional frame-based systems. OBJECTIVE: To compare the accuracy of our streamlined robotic DBS workflow with data in the literature from frame-based and frameless systems. METHODS: We retrospectively reviewed 126 consecutive DBS lead placement procedures using a robotic stereotactic platform. Indications included Parkinson disease (n = 94), essential tremor (n = 21), obsessive compulsive disorder (n = 7), and dystonia (n = 4). Procedures were performed using a stereotactic frame for fixation and the frame pins as skull fiducials for robot registration. We used intraoperative fluoroscopic computed tomography for registration and postplacement verification. RESULTS: The mean radial error for the target point was 1.06 mm (SD: 0.55 mm, range 0.04-2.80 mm) on intraoperative fluoroscopic computed tomography. The mean operative time for an asleep, bilateral implant without implantable pulse generator placement was 238 minutes (SD: 52 minutes), and skin-to-skin procedure time was 116 minutes (SD: 42 minutes). CONCLUSION: We describe a streamlined workflow for DBS lead placement using robot-assisted stereotaxy with a comparable accuracy profile. Obviating the need for checking and switching coordinates, as is standard for frame-based DBS, also reduces the chance for human error and facilitates training.